2010
DOI: 10.1016/j.autrev.2010.03.006
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ Tregs in lupus, autoimmunity, and beyond

Abstract: While CD4+CD25high regulatory T cells (Tregs) have garnered much attention for their role in the maintenance of immune homeostasis, recent findings have shown that subsets of CD8+ T cells (CD8+ Tregs) display immunoregulatory functions as well. Both CD4+ Tregs and CD8+ Tregs appear impaired in number and/or function in several autoimmune diseases and in experimental animal models of autoimmunity, suggesting the possibility of immunotherapeutic targeting of these cells for improved management of autoimmune cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
86
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 151 publications
(183 reference statements)
2
86
1
1
Order By: Relevance
“…Human CD8 + T cells from tolerant, but not control mice exhibited suppressor activity and high expression of BCL6. These data are consistent with recent studies emphasizing the role of CD8 + Ts cells in autoimmunity, transplantation, and infectious diseases (39)(40)(41)(42).…”
Section: Discussionsupporting
confidence: 82%
“…Human CD8 + T cells from tolerant, but not control mice exhibited suppressor activity and high expression of BCL6. These data are consistent with recent studies emphasizing the role of CD8 + Ts cells in autoimmunity, transplantation, and infectious diseases (39)(40)(41)(42).…”
Section: Discussionsupporting
confidence: 82%
“…This might be, at least in part, because of the heterogeneity and complexity of regulatory CD8 T cell subsets, each of which might be involved in different aspects of immune responses (11). Suzuki and colleagues (5) demonstrated that naturally occurring CD8 Tregs expressed CD122, although it was widely accepted that CD122 is a marker of memory CD8 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CD122 + CD8 T cells, various subsets of CD8 T cells were reported to have regulatory activity (9)(10)(11). In earlier studies, it was shown that injecting cyclophosphamide (CP) in mice enhanced immune responses that were suppressed by complementing T cells from nontreated mice (10).…”
mentioning
confidence: 99%
“…These CD8 ? 'Tregs' function in EAE in rodents, the NZB/NZW mouse model of SLE, NOD mouse diabetes, and murine models of myasthenia gravis and rheumatoid arthritis and have been demonstrated in inflammatory bowel disease and multiple sclerosis in humans [90][91][92]. These CD8 ?…”
Section: Self-tolerance To Mrbc Maintained By Regulatory T Cellsmentioning
confidence: 96%
“…Tregs (reviewed in [60,[87][88][89]); however, there are increasing numbers of modern reports of CD8 ? 'Tregs' (reviewed in [90][91][92]). These CD8 ?…”
Section: Self-tolerance To Mrbc Maintained By Regulatory T Cellsmentioning
confidence: 99%